Linear viscous damping in random wave excited gap resonance at laboratory scale — NewWave analysis and reciprocity. (July 2018) - Zhao, Wenhua; Taylor, Paul H.; Wolgamot, Hugh A.; Taylor, Rodney Eatock
Abstract: The resonant response of the water free surface in narrow gaps between two side-by-side vessels in random waves is investigated with both large scale laboratory experiments and computationally with linear diffraction theory. In our previous work we observed that all the damping due to both viscous and wave radiation processes appeared to be linear for each gap resonant mode. The present paper investigates the reciprocity of designer waves (the input wave group selected to give a response in time matching the most probable maximum response) and the associated gap resonant response, providing further support for the proposition that the viscous damping of the gap resonance is linear within the range tested. Within this regime it becomes possible to estimate the amplitude of the gap resonance for different gap widths, without conducting additional experiments. Assuming Stokes boundary layer damping, the viscous damping at a specific gap width can be easily scaled to any other gap widths. The scaled viscous damping, when combined with a parametric fit to the potential flow response transfer functions, enables the prediction of the gap resonance RAOs (response amplitude operators) for different gap widths. The estimated RAOs agree well with the measured data. At laboratory scale, it appears there is always a non-zero gap width giving maximum peak free-surface response. Highlights: Gap resonance between two vessels is investigated. Viscous damping in the gap has a close to linear form for the conditions tested. It is consistent with damping by Stokes oscillatory laminar boundary layers. Gap resonances at different gap widths are predicted by scaling the linear damping. It appears there is always a non-zero gap width giving maximum peak response.